Distributed Ledger Technology and Secured Transactions : Note 1. Collateral Registry, Secured Transactions Law and Practice - World Bank (World Bank, Washington, DC, 2020)
This Guidance Note examines the potential of Distributed Ledger Technology (DLT) within the context of the UNCITRAL Model Law on Secured Transactions. While this model is the primary reference, the Guidance Note also provides examples from domestic secured transactions frameworks, especially where the analysis leads to a different result. It examines these issues from different perspectives, including those of policy makers and legislators but also secured creditors and borrowers. It should be a useful tool not only for stakeholders in economies that contemplate undertaking secured transactions but also for those engaged in secured transactions where DLT plays some role, such as a loan applicant proposing to use as collateral her digital asset for which the secured transactions law does not contain any specific provisions.